2015
DOI: 10.4238/2015.december.16.6
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of survivin, Bcl-2, and KAI1 proteins in cervical cancer and their correlation with metastasis

Abstract: ABSTRACT. Cervical cancer is associated with abnormal expression of multiple genes. Survivin and Bcl-2 proteins are apoptosis inhibitors. The tumor suppressor gene CD82, which encodes the protein KAI1, is downregulated in cervical cancer, and is associated with differentiation degree. We investigated the expression levels of three proteins and their correlation with metastasis in cervical cancer by comparing them in different cervical lesions. Immunohistochemistry was used to detect their three protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
2
31
1
1
Order By: Relevance
“…However, none of these have addressed the relationship between Bcl-2 and cervical cancer. Our study is the first to demonstrate that Bcl-2 also inhibits apoptosis in cervical cancer, identifying it as a potential target for molecular therapy based on regulation by miR-187 (Zhou and Wang, 2015). However, we cannot exclude other BCL-2 independent effects during miR-187-mediated cell apoptosis and requires further investigation.…”
Section: Discussionmentioning
confidence: 84%
“…However, none of these have addressed the relationship between Bcl-2 and cervical cancer. Our study is the first to demonstrate that Bcl-2 also inhibits apoptosis in cervical cancer, identifying it as a potential target for molecular therapy based on regulation by miR-187 (Zhou and Wang, 2015). However, we cannot exclude other BCL-2 independent effects during miR-187-mediated cell apoptosis and requires further investigation.…”
Section: Discussionmentioning
confidence: 84%
“…A progressive down-regulation of CD82 was during colorectal mucosa-adenoma-the primary adenocarcinoma to the liver metastasis [45]. Zhou et al [46] found that CD82 expression was markedly lower in cervical cancer than in the normal cervix, chronic cervicitis, or cervical intraepithelial neoplasia. Reportedly, the promoter CpGSite methylation and LOH of CD82 contributed to its epigenetic repression [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of survivin and Bcl-2, and low expression of KAI1 promotes cervical cancer progress and metastasis. [14] The studies suggest that KAI1 may be used as a promising prognostic marker and a possible therapeutic target for human melanoma. [15] Decreased KAI1 expression has been observed recently in various human cancers, including pancreatic, lung, hepatic, colorectal, breast, ovarian, esophageal, and cervical cancers.…”
Section: Discussionmentioning
confidence: 99%